Congenital Corneal Opacities Associated With Trisomy 8 Mosaicism Syndrome. Issue 12 (December 2018) - Welsh, Christopher; Khalili, Sina; Hazrati, Lili-Naz; Mireskandari, Kamiar
Abstract : Purpose: To describe the clinical, anterior segment optical coherence tomography (OCT) and histopathological features of 2 infants with congenital corneal opacities (CCOs) and undiagnosed trisomy 8 mosaicism syndrome (T8mS). Methods: This is a retrospective case report documenting ocular and systemic findings, imaging, pathology and management of 2 patients with T8mS. Results: An 11-month-old white male infant and a 4-week-old Asian female were initially seen for unilateral and bilateral CCOs, respectively. Corneal examination revealed para-axial anterior stromal opacities with blood vessels. Superficial irregular opacities were seen on OCT, and specular microscopy revealed normal endothelial cell morphology. One eye required superficial keratectomy to clear the visual axis and developed steroid-induced glaucoma in the early postoperative period, successfully treated with goniotomy. Both patients had hyperopia, anisometropia, and amblyopia, which was managed with glasses and patching. Cytogenetic testing (through microarray and fluorescence in situ hybridization) later diagnosed T8mS in both cases. Conclusions: T8mS should be considered in the differential diagnosis for superficial CCOs with blood vessels. Anterior segment OCT can guide management and cytogenetics performed to confirm diagnosis. Systemic associations and, in particular, risk of acute myeloid leukemia and myelodysplastic syndromes warrant prompt diagnosis of this condition.